Peran Sistem Core Tax dalam Meningkatkan Efektivitas Pengelolaan Pelaporan Pajak di KKP XYZ - I Dewa Agung Nanditiya Putra; Made Andy Pradana Sukarta; Gede Teguh Prasetya Muttiwijaya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to identify the challenges faced by XYZ Firm in the tax reporting process using the Core Tax system, and to evaluate the solutions implemented to address those challenges. Core Tax, introduced by the Directorate General of Taxes (DGT), seeks to modernize Indonesia’s tax administration by enhancing efficiency and transparency. However, issues such as system downtime, user adaptation difficulties, and data inconsistencies emerged during its implementation. Through interviews and surveys with tax consultants and employees at XYZ, this study found that a lack of training and outreach was a key obstacle. In response, XYZ implemented intensive training programs, leveraged technology, and improved communication with the DGT to receive technical support. The findings indicate that although challenges persist, the implemented solutions have enhanced the effectiveness of the tax reporting process. This research is expected to provide valuable insights for the development of Indonesia’s tax system and offer practical recommendations for further improvements in the implementation of Core Tax